Genetic risk score to improve prediction and treatment in gestational diabetes mellitus - Tian, Yumeng; Li, Ping (Frontiers in Endocrinology, 2022)
Diabetes mellitus is a chronic disease caused by the interaction of genetics and the environment that can lead to chronic damage to many organ systems. Genome-wide association studies have identified accumulating single-nucleotide polymorphisms related to type 2 diabetes mellitus and gestational diabetes mellitus. Genetic risk score (GRS) has been utilized to evaluate the incidence risk to improve the prediction and optimize treatments. This article reviews the research progress in the use of GRS in diabetes mellitus in recent years and discusses future prospects.